A New Electronic Monitoring Device to Measure Medication Adherence: Usability of the Helping Hand™ - Sabina De Geest; Johan Vanhaecke; Mary Beth Happ; Bart Maes; Fabienne Dobbels; Leentje De Bleser; Birgit Vincke (Sensors, 2010)
The aim of this study was to test the user performance, satisfaction and acceptability of the Helping Hand™ (B&O Medicom) electronic medication adherence monitor. Using a mixed-method design, we studied 11 kidney transplant patients and 10 healthy volunteers during three weeks. Although testing showed positive usability aspects, several areas requiring technical improvement were identified: the most important obstacles to usability and acceptability were the weak sound signal, problems loading the medication, and the fact that only one medication could be used at a time.